KUALITAS KONSISTENSI PENGGUNAAN KOSA KATA MUTAKHIR BAHASA INDONESIA PADA SURAT KABAR REPUBLIKA - Muhammad Sulhan; Dewi Indah Susanti (Jurnal Metamorfosa, 2018)
People have unconsciously mixed up the use of Indonesian with a foreign language in the communication. It might be due to the emerging new Indonesian vocabularies as the impact of the rapid innovation in technology. This study aims to examine the consistency quality of the Indonesian vocabularies in the Republika newspaper. The data of this qualitative research is the form of words or phrases of foreign and Indonesian terms. These were searched with their equivalence in the Great Dictionary of Indonesian Language (KBBI) and in the Glossary of Foreign Terms-Indonesia (GIAI). The results show that 40% of vocabularies used is considered inconsistent and the other 60% is consistent to rate that Republika newspaper is good enough in its consistency quality.